PERBANDINGAN EFEKTIFITAS ANTARA SUSU SAPI DAN SUSU KEDELAI TERHADAP PERTUMBUHAN STREPTOCOCCUS MUTANS (Studi terhadap Mahasiswa Fakultas Kedokteran Gigi Universitas Islam Sultan Agung Semarang) - Ifi Nursari Rosanti; Rama Putranto; Benni Benyamin; Moh Baehaqi (Jurnal Medali, 2013)
Carbohydrates and protein can be used to inhibit S. mutans as a bacteri causes caries. Both nutrients can be found in cow’s or soy milk. The aim of the study is to know the difference in effectiveness between the cow’s milk and soy milk on the Streptococcus mutans growth.The research was designed by group post test only. The independent variables were preparation of cow’s milk and soy milk. The dependent variable was the S. mutans growth measured from the inhibition zone diameter around the Muller Hinton Agar Plate. Data were analyzed by One-way anova.Result of this study showed that the inhibition zone diameter in cow’s milk concentration 80% and 100% were 5.26 mm and 6.17 mm, while in the soy milk were 12.61 mm and 15.11 mm. One-way anova results p = 0.000 explained that cow’s milk and soy milk have a significant difference to the S. mutans growth. Post hoc test showed that soy milk 100% was the most powerful in inhibition of S. mutans growth.The inhibition of soy milk and cow’s milk on the growth of S. mutans tends to increase according to the high concentrations that were used. Key words: cow milk, soy milk, Streptococcus mutans